Anthelmintic effects of condensed tannins on Trichostrongylus colubriformis in experimentally infected sheep - Minho, Alessandro Pelegrine; Gennari, Solange Maria; Do Amarante, Alessandro Francisco Talamine [UNESP]; Abdalla, Adibe Luiz (Universidade Estadual de Londrina, 2010)
Recent surveys have identified anthelmintic effects from many bioactive substances particularly from condensed tannin (CT) sources. The aims of the present study were to investigate the potential anthelmintic effects of condensed tannins (CT) on Trichostrongylus colubriformis in experimentally infected sheep and the nutritional consequences on animals. Twenty helminth-free lambs were divided into five groups of four animals. Groups I to IV were artificially infected with 6,000 third stage larvae (L3) of T. colubriformis. Group I was the infected control and group V was the uninfected control. Twenty-eight days post-infection (p.i.) lambs from GII were supplemented with tanniniferous sorghum (350 g/animal/day, during seven days); GIII were drenched with Acacia mearnsii extract (15% CT) for just one day and GIV during two days (1.6 g extract/kg BW). At day 36 p.i., animals from infected group (GI to GIV) were slaughtered. Faecal egg counts (FEC) values present a reduction on GII when compared with GI at day 29 p.i. (P < 0.05) and between GIII and GI at day 35 and 36 p.i. (P < 0.05). The values of egg hatchability and number of L3 recovered from the faeces were not statistical analyzed (there was no duplicate data), however there was a considerable reduction between the values from treated and control group. The use of CT on diet did not cause significant difference on blood parameters, body-weight and carcass-weight (P > 0.05). No difference was related on total worm burden between treatments; however, GIV presented lower number of females than GI (P < 0.05). The use of CT could be a promising alternative source to reduce the pasture contamination and to control T. colubriformis infection in sheep.
Keywords: Alternative control; Bioactive compounds; Nematode; Ovine; Tannins